Quantifying System-Level Optimizations for Latency and Frame-Time Stability in Real-Time Workloads - Rigoli, Aldrei Casalini; Padoin, Edson Luiz (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS), 2026)
This paper investigates how Windows 11 and GPU driver tuning affect latency-related behavior in a real-time gaming workload. We compare an out-of-the-box profile (OOB) and an optimized profile (OPT) in Counter-Strike 2 (CS2) using PresentMon, FrameView, VProf Lite, and LatencyMon. Across ten deterministic low-preset runs per profile, OPT increases average throughput from 272.64 to 281.61 FPS (+3.29%), but worsens frametime tails (p95: 5.520 to 6.987 ms; p99: 6.017 to 7.795 ms). A complementary preset comparison shows that graphics-load choice has a much larger effect than OS tuning: the high preset drops performance to about 132 FPS with 7.56 ms mean frametime. Overall, the results expose a clear trade-off between average throughput and worst-frame behavior and reinforce the use of tail-aware metrics in latency-sensitive workloads.